Estimates of Unionism and Collective Bargaining in Canada - Kumar, Pradeep (Relations industrielles / Industrial Relations, 1988)
This paper presents new estimates of unionization and collective bargaining coverage for Canada from a special Statistics Canada household survey conducted in December 1984. The new estimates are comparee with the old estimates.